2018
DOI: 10.3390/catal8090375
|View full text |Cite
|
Sign up to set email alerts
|

Ce and Zr Modified WO3-TiO2 Catalysts for Selective Catalytic Reduction of NOx by NH3

Abstract: A series of Ce and/or Zr modified WO3-TiO2 catalysts were synthesized by the impregnation method, which were employed for NH3-SCR reaction. The T50 contour lines of NOx were used to quickly optimize catalyst composition, the Ce20Zr12.5WTi catalyst was considered to be the optimization result, and also exhibited excellent NH3-SCR activity and thermal stability with broad operation temperature window, which is a very promising catalyst for NOx abatement from diesel engine exhaust. The excellent catalytic perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In addition to the above multiplex oxide catalysts, many research papers have reported that CeO 2 was combined with other transition metal oxides to form NH 3 -SCR catalysts, such as Sn 2 O 5 [102], VO x [103], CuO [104], Nb 2 O 5 [105], ZrO 2 [106] and CoO [107]. They can simultaneously enhance the surface acidity, redox performance and SO 2 /H 2 O resistance of the SCR catalysts.…”
Section: Other Cerium-based Multiplex Oxide Catalystsmentioning
confidence: 99%
“…In addition to the above multiplex oxide catalysts, many research papers have reported that CeO 2 was combined with other transition metal oxides to form NH 3 -SCR catalysts, such as Sn 2 O 5 [102], VO x [103], CuO [104], Nb 2 O 5 [105], ZrO 2 [106] and CoO [107]. They can simultaneously enhance the surface acidity, redox performance and SO 2 /H 2 O resistance of the SCR catalysts.…”
Section: Other Cerium-based Multiplex Oxide Catalystsmentioning
confidence: 99%
“…The results for steady-state activity of catalysts were recorded after about 20 min at each temperature. The NOx conversion were calculated accordingly [3], whereas NOx = NO + NO 2 .…”
Section: Activity Evaluationmentioning
confidence: 99%
“…Selective catalytic reduction with ammonia (NH 3 -SCR) has been successfully developed as a promising technology for reducing NOx emitted in combustion gas emissions from automotive sources [1][2][3]. Cu-SSZ-13, with superior activity and durability, has been generally considered as the predominant commercial SCR catalyst applied in North American, European and Chinese diesel vehicles [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ce-containing catalysts have attracted a lot of attention for their superior de-NO X activities that are caused by their unique oxygen storage properties [11][12][13][14][15]. Cao et al [16] prepared a CeO 2 /TiO 2 catalyst with high SCR activity due to enhanced "fast SCR" reactions following the L-H mechanism.…”
Section: Introductionmentioning
confidence: 99%